Predicting working adults’ intention to use e-wallet in Malaysia: a perspective of behavioural belief - Tai, Tien How; Lee, Kenneth Ming Jian; Yap, Yong Yi; Surajvaraman, Krishnan Moorty (2020)
In this era of technological revolution, e-wallet had become one of the main payment methods that were used around the world. However, the usage of this service is still considered moderately low in the context of Malaysia. Up until now, there were limited studies that can be found to examine the intention to use e-wallet for working adults in Malaysia. Hence, this paper aims to determine the effect of behavioural beliefs on their influence towards the intention to use e-wallet of working adults in Malaysia. In this study, the behavioural belief factors such as perceived usefulness, perceived ease of use, perceived security, and trust is examined to identify their relationship with working adult’s intention to use e-wallet, with attitude as a mediating variable. The Theory of Reasoned Action (TRA) is used to construct the conceptual framework. This paper was done in hoping that it will provide as a benchmark to the e-wallet literature by identifying the effect of behavioural belief towards working adults’ intention to use e-wallet, with attitude as the mediator.